Making Design Thinking Work: Adapting an Innovation Approach to Fit a Large Technology-Driven Firm. Issue 5 (3rd September 2019) - Mahmoud-Jouini, Sihem Ben; Fixson, Sebastian K.; Boulet, Didier
Abstract : Overview: In their quest to become more innovative, many firms try out new innovation approaches that are brought in from the outside. Design thinking has been one of these sought-after innovation approaches in recent years. Design thinking has produced remarkable results in creative firms such as design consultancies, but its implementation in large, established firms has proven to be far more challenging, especially if a strong company culture contradicts the philosophies underlying design thinking. One possible answer to this challenge lies in adapting an innovation approach such as design thinking to its new environment so it can truly take hold. We describe how a large, technology-driven firm proceeded in morphing the design thinking approach to allow it to take root in different parts of the company and over time become an integral part of the firm's innovation activity.